# How do you solve #5y - 6+ y + 27= 8y + 30- 5y#?

y=3

Gather similar terms (visit this link if you need help).

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 5y - 6 + y + 27 = 8y + 30 - 5y, first combine like terms on both sides of the equation: 5y + y - 5y - 8y = 6 - 27 + 30 Then, simplify each side: y = 9

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7